International Financing Through Letters of Credit in Trade for Export Activities - Dewi, Ni Kadek Deby Prasetya; Antari, Putu Eva Ditayani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
International trade is a vital foundation of global economic activity, fostering interconnectedness among nations and enabling the exchange of goods, services, and capital across borders. One key financial instrument ensuring security and efficiency in such transactions is the Letter of Credit (L/C). Serving as a payment guarantee, L/C minimizes risks in cross-border trade and builds trust between exporters and importers. This study examines the crucial role of L/C in facilitating international trade, particularly within the agricultural sector, and its legal implications for exporters. It highlights the benefits of L/C, including payment assurance, risk mitigation, and protection from financial constraints such as foreign exchange restrictions. However, challenges persist due to varying interpretations of L/C provisions, procedural differences among banks, and regulatory inconsistencies—especially within Indonesia’s financial system. Moreover, while L/C safeguards against payment default, it does not guarantee the quality or condition of shipped goods, necessitating complementary risk management measures. The study underscores the importance of stronger legal protection and regulatory harmonization to enhance the reliability of L/C in global trade. Ultimately, it calls for policy reforms to address existing regulatory gaps and to promote a more secure, efficient, and sustainable international trading environment.